A study on the sensitivity of microwave imaging for detecting small-width bone fractures - Santos, K. C.; Fernandes, C. A.; Costa, J. R. (2021 15th European Conference on Antennas and Propagation (EuCAP), 2021)
Microwave imaging (MWI) could be a first-responder alternative to X-Rays for detecting fractures in superficial bones like the tibia. However, the low resolution of MWI might be a handicap, therefore it needs to be quantified. A monostatic radar-type configuration is adopted in this study, where a Vivaldi antenna operating in the 8.3-11.1 GHz frequency range is used to scan the bone in the near-field. The study uses full-wave simulations to acquire the antenna s11 vs frequency at all scanning points. The bone is modeled as a multilayer dielectric structure with appropriate permittivity values to represent the bone structures and covering tissues. The image is reconstructed using a matched filter technique. Results show that the proposed system can detect transversal bone fractures as thin as 0.25 mm in superficial bones.